Assessing the economic cost of depleting groundwater in Balochistan: A Social Accounting Matrix (SAM) multiplier approach - Rizwan, Noormah; Shikoh, Sania Haider; Davies, Stephen; Moeen, Muhammad Saad; Rana, Abdul Wajid; Haider, Zeeshan (International Food Policy Research Institute, 2021)
Prolonged droughts and depleting groundwater resources have been a serious challenge to the economy of province of Balochistan, Pakistan. Proliferation of tube-wells incentivized by government interventions and continued subsidy for electric tube-wells for agriculture and choice for high-water consumption crops have led to steep decline in water tables. This paper uses Social Accounting Matrix (SAM) Multiplier model approach to simulate impact of declining water tables on the provincial economy, a first ever effort. To capture the impact of declining water tables, increase in shadow prices of groundwater are calculated and the effects are traced on agricultural production. Using these effects, simulations are designed to reflect the impact of water tables’ decline on macroeconomic variables including GDP, government’s revenues/expenditures, households’ income, and net exports. Agricultural options are also introduced in the model to explore their effectiveness in mitigating the effects of groundwater exploitation. Effects of non-agricultural options such as the debated removal of tube-well subsidy, shifting to non-agricultural sectors and investment in recharge mechanisms are also estimated on the overall provincial economy. Findings from the paper indicate that depleting water tables have adversely affected the provincial economy and the impact of widely recommended agricultural is moderate in mitigating these effects. Subsidy rationalization is observed to have substantial impact on GDP, households, and trade balance. However, investment in recharge mechanisms and expansion in processing, manufacturing and services sector can be crucial for the development of the province.